Robust formulations for production optimization of satellite oil wells. Issue 5 (4th May 2017) - Hülse, Eduardo Otte; Camponogara, Eduardo
ABSTRACT: In the daily operation of oilfields operators are always seeking for the best operating conditions. In various situations, a drop in processing capacity is incurred by equipment failure, and prediction models are subject to uncertainty, making optimal decisions challenging. Therefore technical works have used mathematical optimization to find the optimal operation in those situations. However, uncertainty has been mostly overlooked and solutions often rely on nominal or average behaviour models. Neglecting the inherent uncertainty can impact the operating practices significantly. To this end, this work reformulates the uncertain production optimization problem as a robust optimization problem following the column-wise and row-wise frameworks, with cardinality-constrained sets. The latter allows the operator to regulate the level of protection of a solution against the uncertain model. The focus is on oilfields producing from satellite wells and with gas-lift systems. The formulations are analysed in a representative oilfield available in simulation software.